Pelatihan dan Implementasi Aplikasi Kependudukan Berbasis Web sebagai Inovasi Layanan Publik di Desa Ngusikan - Anandita, Septian Ragil; Widya, Moh. Anshori Aris; Sujono, Sujono; Huda, Luqman Nur; Prakasa, Wahyu Adi; Jati, Sundaru; Bukhori, Imam; Ulum, Miftahul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This article discusses the community service activities carried out in Ngusikan Village through training and the implementation of a web-based population application. This activity aims to increase the efficiency of population data management in the village. The program includes training for village officials and launching a user-friendly web-based application designed to simplify the recording and management of population data. The results show that village officials can operate the application well, contributing to the improvement of public services and administrative management in Ngusikan Village.